IMPORTANCE OF PROFESSIONAL DEVELOPMENT FOR TEACHERS: IMPORTANCE OF PROFESSIONAL DEVELOPMENT FOR TEACHERS - Tajieva, Aliya; Ilyasova , Muxabbat (Журнал иностранных языков и лингвистики, 2025)
success in the workplace and this process is called professional development. According to Wikipedia.com: “Professional development refers to skills required for maintaining for career path or to general skills offered through continuing education, including the more general skills area of personal development. It encompasses all types of facilitated learning opportunities, ranging from college degrees to formal coursework, conferences and informal learning opportunities situated in practice”